The Influence of Copper and Silver Nanocolloids on the Quality of Pressed Spring Rapeseed Oil - Magdalena Kachel; Arkadiusz Matwijczuk; Agnieszka Sujak; Grzegorz Czernel; Agnieszka Niemczynowicz; Aldona Nowicka (Agronomy, 2019)
The aim of this study was to evaluate the quality of virgin oil pressed from spring rape seeds cultivated with the use of colloidal nanosilver and nanocopper solutions for processing seeds and as foliar fertilizer. The results show that the use of nanometals for seed processing and foliar fertilization increased the content of carotenoid pigments in the oil. The pigment concentration was higher compared to oil pressed from control seeds. The application of nanocolloids onto the seeds and subsequently on the growing plants contributed to the increase of the oxidative stability of oils. Both the acid number (AN) and peroxide number (PN) values were higher in the studied oils as compared to the control, but did not exceed the required allowable levels. Increased content of silver ions and slightly increased copper content was observed in the pressed oil. An infrared spectral analysis (Fourier-Transformed Infra-Red) conducted in combination with chemometrics allowed the classification of the studied oils in terms of their chemical composition. The analysis revealed the presence of bands characteristic of Cu-O-H vibrations after soaking the seeds and spraying the plants with copper nanocolloid, and of C-O-Ag after fertilization with silver nanocolloid.